Effect of Oral Administration of Bromelain on Postoperative Discomfort After Third Molar Surgery. Issue 2 (March 2017) - Ghensi, Paolo; Cucchi, Alessandro; Creminelli, Luca; Tomasi, Cristiano; Zavan, Barbara; Maiorana, Carlo
Abstract : Introduction: The purpose of this prospective randomized controlled clinical trial was to evaluate the effect of oral administration of bromelain on discomfort after mandibular third molar surgery. Materials and Methods: Eighty-four consecutive patients requiring surgical removal of a single mandibular impacted third molar under local anesthesia were randomly assigned to receiving no drug (control group, Group A), postoperative 40 mg bromelain every 6 hours for 6 days (Group B), preoperative 4 mg dexamethasone sodium phosphate as a submucosal injection (Group C), and preoperative 4 mg dexamethasone sodium phosphate as a submucosal injection plus postoperative 40 mg bromelain every 6 hours for 6 days (Group D). Standardized surgical and analgesic protocols were adopted. Maximum interincisal distance and facial contours were measured at baseline and on postoperative days 2 and 7. Pain was measured objectively by counting the number of analgesic tablets required. Patient perception of the severity of symptoms was assessed with a follow-up questionnaire (PoSSe scale). Results: On postoperative day 2, there was a statistically significant reduction in facial edema in both Groups C and D compared with the control group, but no statistically significant differences were observed between Group B and the control group. At evaluation on postoperative day 7, Group D showed a statistically significant reduction in postoperative swelling compared with the control group. The combined use of bromelain and dexamethasone (Group D) induced a statistically significant reduction in the total number of analgesic tablets taken after surgery compared with the control group. The treatment groups had a limited, nonsignificant effect on trismus when compared with the control group. Conclusions: Bromelain used singly showed moderate anti-inflammatory efficacy, reducing postoperative swelling, albeit not to any significant extent compared with no drug administration. The combined use of bromelain and dexamethasone sodium phosphate yielded the best results in terms of control of postoperative discomfort.